Maḥbūb al-qulūb. Volume 2 : Al-Maqāla al-thāniya fi aḥwāl ḥukamāʾ al-Islām wal-ʿulamāʾ al-aʿlām wal-udabāʾ al-kirām mimman lahum al-iʿtināʾ bi-shaʾnihim wal-iʿtibār bi-kalāmihim - Lāhijī, Quṭb al-Dīn Ishkawarī (Miras Maktoob, ISBN: 9789004365452., 2019)
In the Islamic world, the writing of biographical reference works has a very long tradition. In the field of philosophy and other rational sciences such as medicine, one could, for example, mention Isḥāq b. Ḥunayn's (d. 298/910) Taʾrīkh al-aṭibbāʾ wal-ḥukamāʾ or Ibn Abī Uṣaybiʿa's (d. ca 668/1270) ʿUyūn al-anbāʾ fī taʾrīkh al-aṭibbāʾ . The present two-volume biographical dictionary of philosophers and physicians of all times thus continues a centuries-old tradition. Its author, Quṭb al-Dīn Ishkawarī Lāhijī (d. ca. 1088-95/1677-78), was a student of the great Safavi thinker and founder of the School of Isfahan in philosophy, Mīr Dāmād (d. 1041/1631). This is also obvious from his spiritually-orientated, inclusive understanding of the various actors and episodes in the history of philosophy. Written in classical Arabic, at times sprinkled with his native Persian, it distinguishes itself from earlier dictionaries in that it also contains many of the author's own philosophical opinions. 2 vols; volume 2.